Percent of body fat, fat-mass, fat-free mass and assessment of body composition among rural school-going children of Eastern-India - Debnath Sampriti; Mondal Nitish; Sen Jaydip (Anthropological Review, 2018)
Percent of body fat (PBF), fat mass (FM) and fat free mass (FFM) are useful indicators for the assessment of body composition. The present study was conducted among 1351 children (boys: 660; girls: 691) aged 5-12 years residing in West Bengal, Eastern-India. The children were selected using a stratified random sampling method. Anthropometric measurements of height, weight, triceps skinfold (TSF) and sub-scapular skinfold (SSF) were recorded using standard procedures. The PBF, PBF-for-age z-score (PBFZ) and body mass index (BMI) were subsequently calculated. Body composition was assessed using FM, FFM, fat mass index (FMI) and fat free mass index (FFMI). Age-specific mean values of FM ranged from 2.12-4.00 kg (boys) and 2.16-4.40 kg (girls). Age-specific mean values of FFM ranged from 14.45-23.93 kg (boys) and 14.01-23.03 kg (girls). Sex-specific mean differences between sexes were statistically significant in weight, height, TSF, SSF, PBF, PBFAZ, FM, FFM, FMI and FFMI (p<0.05), except in BMI (p>0.05). These results are important for future investigations in clinical and epidemiological settings so as to accurately identify the risk of lower or higher adiposity and body composition using PBF, FM and FFM.